Status of implementation of Framework Convention on Tobacco Control (FCTC) in Ghana: a qualitative study - Lewis Sarah; McNeill Ann; Owusu-Dabo Ellis; Gilmore Anna; Britton John (BMC, 2010)
Abstract Background The Framework Convention on Tobacco Control (FCTC), a World Health Organization treaty, has now been ratified by over 165 countries. However there are concerns that implementing the Articles of the treaty may prove difficult, particularly in the developing world. In this study we have used qualitative methods to explore the extent to which the FCTC has been implemented in Ghana, a developing country that was 39th to ratify the FCTC, and identify barriers to effective FCTC implementation in low income countries. Methods Semi-structured interviews with 20 members of the national steering committee for tobacco control in Ghana, the official multi-disciplinary team with responsibility for tobacco control advocacy and policy formulation, were conducted. The Framework method for analysis and NVivo software were used to identify key issues relating to the awareness of the FCTC and the key challenges and achievements in Ghana to date. Results Interviewees had good knowledge of the content of the FCTC, and reported that although Ghana had no explicitly written policy on tobacco control, the Ministry of Health had issued several tobacco control directives before and since ratification. A national tobacco control bill has been drafted but has not been implemented. Challenges identified included the absence of a legal framework for implementing the FCTC, and a lack of adequate resources and prioritisation of tobacco control efforts, leading to slow implementation of the treaty. Conclusion Whilst Ghana has ratified the FCTC, there is an urgent need for action to pass a national tobacco control bill into law to enable it to implement the treaty, sustain tobacco control efforts and prevent Ghana's further involvement in the global tobacco epidemic.